Dampak Game Online Terhadap Kebugaran Jasmani Siswa Sekolah Dasar Negeri Simpang Empat 2 - Alifandi, Muhammad Ridho; Dirgantoro, Edwin Wahyu; Fauzan, Lazuardy Akbar (Institut Teknologi Bandung, 2025)
This study aims to analyze the impact of online gaming on physical fitness by exploring the relationship between the duration of gaming and physical health. The research employed a correlational method with a quantitative approach, and participants were selected using purposive sampling. The instrument used in this. study was the Nusantara Student Fitness Test (TKPN), which included a series of tests such as the V Sit and Reach, Squat Thrust, Sit-Up, and PACER Test. Data were analyzed using non-parametric statistical methods, specifically Spearman’s correlation. The results revealed that there was no significant relationship between online gaming and physical fitness, with a significance value of 0.111 (> 0.05) and a correlation coefficient of 0.266. This indicates a very weak and statistically insignificant relationship between the two variables. In conclusion, there is no significant correlation between online gaming and the physical fitness levels of students